2020
DOI: 10.1038/s41598-020-68850-1
|View full text |Cite
|
Sign up to set email alerts
|

Nucleosome binding by the pioneer transcription factor OCT4

Abstract: The crosslinked peptides were identified using the xQuest/xProphet software (https ://prote omics .ethz.ch/) 51 , and the crosslinks were visualized using the webserver xVis (https ://xvis.genze ntrum .lmu.de/ login .php) 53. The mass spectrometry raw data used in this study have been deposited to the proteomeXchange Consortium via the JPOST repository (PXD019160, https ://prote omece ntral .prote omexc hange .org/cgi/GetDa taset ?ID=PXD01 9160) 54. Data accessibility The cryo-EM map of the LIN28B nucleosome h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
31
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 57 publications
(86 reference statements)
12
31
0
Order By: Relevance
“…It was found that 9 out of the 13 TFs are predicted to have end preference including OCT4/POU5F1 and p53. This result is consistent with previous studies that these two proteins interact with the end of nucleosomal DNA [ 30 , 31 ].…”
Section: Resultssupporting
confidence: 94%
“…It was found that 9 out of the 13 TFs are predicted to have end preference including OCT4/POU5F1 and p53. This result is consistent with previous studies that these two proteins interact with the end of nucleosomal DNA [ 30 , 31 ].…”
Section: Resultssupporting
confidence: 94%
“…Furthermore, mutating each site individually revealed that each site contributes to Oct4's affinity for the LIN28B nucleosome except the Sox site and HD -1 sites (Figure 1C, right panel; Figure S1). It also showed that HD -7 is the primary Oct4 binding site in agreement with two recent studies that also reported Oct4 binding to the HD -7 site (16,18). The sites previously proposed by Soufi et al (10, 11) HD -4.5 and S -1.5 are secondary binding sites.…”
Section: Resultssupporting
confidence: 89%
“…The histone tails were not resolved in these structures. Recently, Echigoya et al resolved the structure of a genomic nucleosome bound by Oct4 in the absence of Oct4 and revealed an Oct4 binding site different that those described by Soufi et al (18). In addition, they showed that Oct4 interacts with the histone H3 and competes with the linker histone for binding.…”
Section: Introductionmentioning
confidence: 91%
See 1 more Smart Citation
“…The promoters of eukaryotes contain various sites with different a nity for the binding of diverse transcription factors. Transcription factors bind to speci c DNA sequences in the promoter regions of genes to activate or repress transcription of multiple target genes (Echigoya et al 2020;Kim and O'Shea 2008). We performed additional detailed truncation analysis of the promoter region in HEK-293, U87, and SH-SY5Y cell lines.…”
Section: Discussionmentioning
confidence: 99%